Renomalization of the NN interaction at NNLO: Uncoupled peripheral waves - Timoteo, Varese S.; Frederico, Tobias; Tomio, Lauro [UNESP]; Delfino, Antonio (World Scientific Publ Co Pte Ltd, 2007)
We apply the subtractive renormalization method to the nucleon-nucleon interaction at Next-to-Next-to-Leading order (NNLO). Here we show the results for some uncoupled peripheral waves.